Exercise-Induced Autophagy Suppresses Sarcopenia Through Akt/mTOR and Akt/FoxO3a Signal Pathways and AMPK-Mediated Mitochondrial Quality Control - Zeng, Zhengzhong; Liang, Jiling; Wu, Liangwen; Zhang, Hu; Lv, Jun; Chen, Ning (Frontiers in Physiology, 2020)
Exercise training is one of the most effective interventional strategies for sarcopenia in aged people. Nevertheless, the underlying mechanisms are not well recognized. Increasing studies have reported abnormal regulation of autophagy in aged skeletal muscle. Our current study aims to explore the efficiency of exercise interventions including treadmill exercise, resistance exercise, alternating exercise with treadmill running and resistance exercise, as well as voluntary wheel running on sarcopenia of 21-month-old rats, and underlying mechanisms. Results showed the declined mass of gastrocnemius muscle with deficient autophagy and excessive apoptosis as a result of up-regulated Atrogin-1 and MuRF1, declined Beclin1 level and LC3-II/LC3-I ratio, accumulated p62, increased Bax and reduced Bcl-2 levels, and also exhibited the defective mitochondrial quality control due to declined PGC-1α, Mfn2, Drp1 and PINK1 levels. However, 12-week exercise interventions suppressed the decline in mass loss of skeletal muscle, accompanied by down-regulated Atrogin-1 and MuRF1, increased Beclin1 level, improved LC3-II/LC3-I ratio, declined p62 level, and reduced Bax and increased Bcl-2 level, as well as enhanced mitochondrial function due to the increased PGC-1α, Mfn2, Drp1 and PINK1 levels. Moreover, exercise interventions also down-regulated the phosphorylation of Akt, mTOR and FoxO3a, and up-regulated phosphorylated AMPK to regulate the functional status of autophagy and mitochondrial quality control. Therefore, exercise-induced autophagy is beneficial for rescuing sarcopenia by modulating Akt/mTOR and Akt/FoxO3a signal pathways and AMPK-mediated mitochondrial quality control, and resistance exercise exhibits the best interventional efficiency.